Perencanaan dan Pengendalian Bahan Baku Produk Balsem Bokashi di PT Karya Pak Oles Tokcer Company Group - I Gusti Agung Kade Suriadi; Ni Made Cyntia Utami; Putu Yoga Sastraguna (Study Program of Industrial Engineering, Udayana University, 2023)
PT Karya Pak Oles Tokcer Group Bali is a pharmaceutical company that sells bokashi balm products in the Bali area. However, this product has faced several problems in the ups and downs of demand. This causes a decrease in the quality of raw materials and the large savings costs incurred by the company. Therefore, this research was carried out to forecast demand for bokashi balm products for 1 year and know the most optimal lot-sizing technique for determining the planning and controlling of raw material supplies. This research was conducted using ABC analysis, demand forecasting, and supply planning analysis using the Lot for Lot, Silver Meal, and Least Unit Cost methods. Based on the research, it was found that forecasting results for bokashi balm products measuring 15 grams and 7.5 grams using the Moving Average method for the ninth and eighth periods were the best results. Then from the results of the ABC analysis, it was found that for the 15-gram bokashi balm product, the raw materials belonged to category A, namely packaging boxes, pot lids, pots, and top and bottom labels. In contrast, for the 7.5-gram product, there were raw materials in the form of packaging boxes, lids pots, pots, top and bottom labels, and bulbs. Raw materials belonging to group A will then be calculated using the Material Requirement Planning (MRP) method. Then after calculating using 3 lot sizing methods, the Lot for Lot (LFL) method was chosen because it has the smallest total cost value, namely the 15-gram bokashi balm product of IDR 2,306,369 and the 7.5-gram bokashi balm product in the amount of IDR 4,079,780.